The Speech Processing Lexicon 2017
DOI: 10.1515/9783110422658-005
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry or asymmetry: Evidence for underspecification in the mental lexicon

Abstract: We focus here on asymmetries which are part and parcel of phonological systems of natural language. We provide an overview of our assumptions concerning asymmetric representations, which are abstract and underspecificied, outlining the principles underpinning the Featurally Underspecified Lexicon (FUL;Lahiri & Reetz, 2002, 2010 and illustrating how questions regarding the specificity of lexical representations can be translated into experimental paradigms addressing processing issues. The second half of the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
2
5
0
1
Order By: Relevance
“… Roberts et al, 2014 ; Kotzor et al, 2017a ) also confirmed this asymmetric processing pattern. Roberts et al (2014) used a cross-modal semantic priming paradigm with EEG which showed activation patterns in line with the behavioural experiments in Kotzor et al (2017a , 2017b) , with similar N400 attenuation for real words and singletons which were mispronounced as geminates but no N400 reduction for original geminates where the medial vowel was shortened to a singleton. The same asymmetric pattern was also found in pre-attentive processing in a standard oddball paradigm indicated by a difference in the mismatch negativity (MMN) component ( Kotzor et al, 2017a ).…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“… Roberts et al, 2014 ; Kotzor et al, 2017a ) also confirmed this asymmetric processing pattern. Roberts et al (2014) used a cross-modal semantic priming paradigm with EEG which showed activation patterns in line with the behavioural experiments in Kotzor et al (2017a , 2017b) , with similar N400 attenuation for real words and singletons which were mispronounced as geminates but no N400 reduction for original geminates where the medial vowel was shortened to a singleton. The same asymmetric pattern was also found in pre-attentive processing in a standard oddball paradigm indicated by a difference in the mismatch negativity (MMN) component ( Kotzor et al, 2017a ).…”
Section: Introductionsupporting
confidence: 56%
“…Recent psycholinguistic and neurolinguistic studies (cf. Roberts et al, 2014 ; Kotzor et al, 2016a , 2016b & 2017a , 2017b ) have argued for a privative representation of duration where a monovalent feature is either present in a segment or absent. This proposal is based on experimental evidence from languages with underlying duration contrasts (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Näätänen & Picton, 1987;Näätänen, 2001;Näätänen et al, 2007 for a review), has previously shown sensitivity to differences on the level of phonological representation and has thus been a key component in establishing processing asymmetries such as those discussed above (cf. Eulitz & Lahiri, 2004;Cornell et al, 2011;Roberts et al, 2013;de Jonge & Boersma, 2015;Kotzor et al, 2017;Højlund et al 2019).…”
Section: Mismatch Negativity (Mmn)mentioning
confidence: 99%